2013
DOI: 10.1097/sih.0b013e31829068df
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Expert and Novice Performance of a Simulated Transesophageal Echocardiography Examination

Abstract: A simulated transesophageal examination of normal cardiac anatomy in concert with a standardized assessment tool permits ample discrimination between expert and novice echocardiographers as defined for this investigation. Future research will examine in detail the role echocardiography simulators should play during echocardiography training including assessment of training level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…In addition, many studies used convenience samples that were not powered, and none of the studies calculated the number of participants required to achieve statistical significance, with one study commenting that their study was not adequately powered to detect differences between their two academic sites. 55 Many of the studies (n=13) were pilots or had small numbers (<50) of participants (range: n=18 to n=45). A small number of studies were conducted across different health centers 55 57 ; however, the majority of these were conducted in a single health setting or university, making it difficult to generalize the findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies used convenience samples that were not powered, and none of the studies calculated the number of participants required to achieve statistical significance, with one study commenting that their study was not adequately powered to detect differences between their two academic sites. 55 Many of the studies (n=13) were pilots or had small numbers (<50) of participants (range: n=18 to n=45). A small number of studies were conducted across different health centers 55 57 ; however, the majority of these were conducted in a single health setting or university, making it difficult to generalize the findings.…”
Section: Methodsmentioning
confidence: 99%
“… 55 Many of the studies (n=13) were pilots or had small numbers (<50) of participants (range: n=18 to n=45). A small number of studies were conducted across different health centers 55 57 ; however, the majority of these were conducted in a single health setting or university, making it difficult to generalize the findings. The included articles had scores on the critical appraisal tool ranging from 8 to 14/15.…”
Section: Methodsmentioning
confidence: 99%
“…Experience and expertise are valuable to employers; for example, 81% of U.S. employers pay for and encourage their employees to learn and enhance their skill sets (Germain 2011), but how are experts distinguished from novice employees. Simulators have been used extensively in the medical field for training, as well as for studies investigating the difference in performance between different experience levels (Bick et al 2013;Conway et al 2014;Mandava et al 2015). None of these studies found here have distinguished any type of distributions for either the novice or expert sample groups (Ueda et al 2010;Bick et al 2013;Conway et al 2014;Mandava et al 2015;Mazomenos et al 2016;Cahill et al 2018).…”
Section: Introductionmentioning
confidence: 83%
“…Simulators have been used extensively in the medical field for training, as well as for studies investigating the difference in performance between different experience levels (Bick et al 2013;Conway et al 2014;Mandava et al 2015). None of these studies found here have distinguished any type of distributions for either the novice or expert sample groups (Ueda et al 2010;Bick et al 2013;Conway et al 2014;Mandava et al 2015;Mazomenos et al 2016;Cahill et al 2018). One paper that studied expert and novice performs in a specific task that neither had extensive experience in, found that there were a few cases where the students had a higher performance value than the experts, but overall the experts had a lower variance.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we: i) describe the development of a tool to assess global quality of published genetic association studies, ii) evaluate the tool’s reliability and validity, and iii) investigate whether the reliability and validity of the tool differs based on user’s familiarity with genetic association studies, since there is some evidence to suggest that experts outperform novices on evaluations involving knowledge across different content areas [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%